Diapause Termination and Postdiapause in Lygus hesperus (Heteroptera: Miridae). Issue 1 (5th January 2021) - Brent, Colin S
Abstract: The western tarnished plant bug, Lygus hesperus Knight, overwinters as a diapausing adult in response to short day lengths. Once environmental conditions are favorable, the bugs revert to an active reproductive state. To determine the impact on life-history traits of diverting resources toward diapause rather than oogenesis during early adulthood, diapausing and nondiapausing L. hesperus females were reared from the same cohorts. Body mass, ovarian maturation, ovipositional activity, and survivorship were monitored starting either at the time of release from diapause-inducing conditions or at adult eclosion for diapausers and nondiapausers, respectively. Females that had gone through 2 wk of diapause were larger and able to mobilize the resources necessary for oogenesis faster than nondiapausers, initiating oogenesis and ovipositing sooner and at a faster initial rate. However, lifetime egg production and average daily rates were similar for both groups. Postdiapausers lived longer than nondiapausers by an average of 19 d, which is five more than the 2-wk period when they were reproductively senescent. Overall, the results indicate that short-term diapause does not have a negative impact on life history. Furthermore, the extra endogenous resources stored during diapause may be able to enhance the alacrity with which the female can take advantage of improved environmental conditions and may prolong life by shielding the females against environmental stressors such as temperature extremes, oxidative agents, or food deficits.